Vocalization Behavior and Calling Phenology in Two Direct-developing Frogs of the genus Oreobates of Yungas Andean Forests in Northwest Argentina - Akmentins, Mauricio Sebastián (2023)
Calling activity directly affects male mating success in anurans; thus, it is expected that the maximum calling effort would be allocated during the most favorable conditions to breed. We described the diel activity pattern and the calling phenology of two sympatric allotopic direct-developing frog species of the genus Oreobates, Baritú?s Robber Frog (O. barituensis) and Confused Robber Frog (O. berdemenos) in a subtropical montane forest of northwestern Argentina. We assessed the influence of abiotic environmental cues of temperature and air humidity at the microhabitat scale on the advertisement call emission of both species. We monitored the calling behavior at two locations near each other with passive acoustic monitoring surveys. We fitted generalized linear mixed models to determine the relationships between the calling activity and the abiotic environmental variables. We found remarkable interspecific differences in the calling behavior of these direct-developing frogs during the reproductive season, where O. barituensis showed a crepuscular/nocturnal activity without chorus formation in a non-continuous and short calling season, while O. berdemenos showed a broad diel vocalization pattern with chorusing behavior in an extended and continuous calling season. Environmental cues influenced advertisement call emission at the microhabitat scale; both species showed a negative relationship with temperature. Vocal activity of O. berdemenos also showed a negative relationship with air humidity and a positive relationship with time of the day. We emphasized the importance of considering calling effort as a population parameter in studies of anuran calling behavior.